Get set for mental health impact - Abdul Razak, Dzulkifli (Sun Media Corporation Sdn Bhd, 2020)
The tabligh issue seems to have gone beyond the health dimension. Some politicians are blaming others and trying to claim credit while the rakyat are anxious to know when the outbreak will end. This could be the reason why once things are under control, thanks mostly to the technocrats headed by Datuk Dr Noor Hisham Abdullah and his dedicated team, the politicians are keen to steal the thunder.